Is the BNT162b2 COVID-19 vaccine effective in elderly populations? Results from population data from Bavaria, Germany - Gomes, Delphina; Beyerlein, Andreas; Katz, Katharina; Hoelscher, Gabriele; Nennstiel, Uta; Liebl, Bernhard; Überla, Klaus; Von Kries, Ruediger (PLoS ONE, 2021)
Background
CRIS-Team WoS Importer:2022-02-25